Application of clinical blood metabogram for diagnosis of early-stage Parkinson’s disease: a pilot study - Lokhov, Petr G.; Trifonova, Oxana P.; Balashova, Elena E.; Maslov, Dmitry L.; Ugrumov, Michael V.; Archakov, Alexander I. (Frontiers in Molecular Biosciences, 2024)
In terms of time, cost, and reproducibility of clinical laboratory tests, a mass spectrometric clinical blood metabogram (CBM) enables the investigation of the blood metabolome. Metabogram's components provide clinically relevant information by describing related groups of blood metabolites connected to humoral regulation, the metabolism of lipids, carbohydrates and amines, lipid intake into the organism, and liver function. For further development of the CBM approach, the ability of CBM to detect metabolic changes in the blood in the early stages of Parkinson's disease (PD) was studied in this work. In a case-control study (n = 56), CBM enabled the detection of the signature in blood metabolites related to 1-2.5 clinical stages of PD, according to the modified Hoehn and Yahr scale, which is formed by alterations in eicosanoids, phospholipids and, presumably, in the butadione metabolism. The CBM component-based diagnostic accuracy reached 77%, with a specificity of 71% and sensitivity of 82%. The research results extend the range of disorders for which CBM is applicable and offer new opportunities for revealing PD-specific metabolic alterations and diagnosing early-stage PD.